T-Resveratrol Protects Against Acute High Glucose Damage in Endothelial Cells - Martinez-Salinas, J (Springer New York LLC, 2018)
Postprandial hyperglycemia in diabetic and nondiabetic subjects is associated with endothelial dysfunction. Evidence shows that high glucose generates oxidative stress and a pro-inflammatory state promoting the development of cardiovascular diseases. trans-Resveratrol (t-RV) has been shown to reduce cardiovascular risk. To determine whether t-RV acts as a protector against acute high glucose (AHG)-induced damage, two in vitro models, rat aortic rings (RAR) and human umbilical vein endothelial cells (HUVEC) were used. RAR pretreated with AHG (25 mM D-glucose) for 3 h dramatically decreased the endothelium-dependent relaxation (EDR) induced by acetylcholine in phenylephrine (PE)-precontracted vessels. However, coincubation with t-RV significantly mitigated the damage induced by AHG on EDR. Pretreatment with AHG did not affect the vasodilation induced by sodium nitroprusside. HUVEC treated with t-RV decreased cytotoxicity and reduced radical oxygen species production induced by AHG. Taken together, these results suggest that t-RV can mitigate the AHG-induced EDR damage through a mechanism involving ROS scavenging and probably an increase in the bioavailability of NO. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.